Capital structure on firm's performance: Focusing on technological sector in Malaysia / Ummi Mariah Ismail - Ismail, Ummi Mariah (2018)
This research presents a study that focusing on interdependency of determinants of capital structure in technological sector firms listed in Bursa Malaysia. Capital structure is playing an important role in the companies. In addition, capital is the primary resources for the firms and they can be from debt and also equity. The determinants were chosen based on suitability of the research. The independent variables art long term debt, short term debt, total debt, tangibility and firm size whereas the dependent variable is return on equity. This research utilizes a panel data which are from 20122017 for six years and different eleven firms in technological sector. The sample aim this study are collected front financial reports in Bursa Malaysia website only. All the data are on the Malaysian Ringgit (MYR) unit. The objective of this study is to examine the relationship between selected independent variables towards the dependent variable. Based on the result, it is found that the selected independent variables have positive relationship With the dependent variable.